The Mental Genome of Athletic Performance: Decoding Confidence, Focus, and Resilience across Athletic Disciplines in School-Level Athletes - Manjula, C.; Suganya, S. (Journal of Neonatal Surgery, 2025)
Psychological traits play a crucial role in shaping athletic performance, particularly during formative school years when athletes are developing both physically and mentally. This study explores the discipline-specific psychological traits of school-level athletes and their influence on performance across throwing, jumping, and running events. A total of 150 athletes aged 12–18 years, evenly distributed among the three disciplines, were assessed for key psychological attributes including self-confidence, focus, and resilience. Standardized tools such as the Psychological Performance Inventory (PPI) and the Competitive State Anxiety Inventory-2 (CSAI-2) were employed to evaluate these traits. Performance was measured through athletes’ personal bests and competition rankings. The study aims to highlight the importance of aligning psychological training with the unique demands of each athletic discipline, offering insights to inform more effective mental conditioning programs in school sports environments.